Study on the Prevalence of Extended-spectrum B-lactamase in Pseudomonas aeruginosa in the Tertiary Care Center, India - Swati Tewari; Alok Kumar; Ekta Rani (Innovations in Microbiology and Biotechnology Vol. 3, 2022)
Aims: The present study was undertaken to determine the prevalence of ESBL-production among the clinical isolates of Pseudomonas aeruginosa. Introduction: Pseudomonas aeruginosa is an opportunistic nosocomial pathogen, and its increasing resistance to broad-spectrum beta-lactams, mediated by extended-spectrum beta-lactamase enzymes (ESBL), is a global concern. Materials and Methods: Various clinical specimens were processed in our laboratory, and Pseudomonas aeruginosa was identified using standard microbiological procedures. An ESBL screening test was performed on all isolates. The potential ESBL producer was then subjected to an ESBL phenotypic confirmatory test using the Disc Diffusion method. All confirmed isolates were subjected to an antimicrobial susceptibility test using the Kirby – Bauer disc diffusion method, in accordance with Clinical Laboratory Standard Institute (CLSI 2016) guidelines. Results: During the study period, 322 non-duplicate isolates of Pseudomonas aeruginosa were identified. ESBL production was found in 26.09 percent (n = 84) of the Pseudomonas aeruginosa isolates. All ESBL positive Pseudomonas aeruginosa isolates were resistant to ciprofloxacin 79 (94.05%), Gentamicin 61 (72.62%), and tobramycin 60 (71.43%). Resistance was low to drugs like cefoperazone + sulbactam 17 (20.24%) and piperacillin + Tazobactam 14 (16.67%), and Imipenem 15 (17.86%). All the isolates showed 100% sensitivity to Polymyxin B. Conclusion: Present study highlights the prevalence and drug resistance of ESBL positive Pseudomonas aeruginosa. Regular antimicrobial susceptibility testing is required for the judicious use of antibiotics in order to prevent the spread of drug resistance.